Urban expansion and social vulnerability in União dos Palmares/AL-A expansão urbana e a vulnerabilidade social em União dos Palmares/AL - Reynaldo Daivyd Lopes da Silva; Thaís Patricia Paulino da Silva; Claudionor de Oliveira Silva (Universidade Estadual de Alagoas, 2020)
Over time, urban space tends to expand at a considerable, speed, while social, development is a slow and disproportionate element. The objective of this article is to study urban expansion and social vulnerability that are directly related to socioeconomic factors. The methodology has a qualiquantitavo, character based on applications of questionnaires and observations in the field, and informal interviews with residents of areas with lower socioeconomic investment are still necessary. The results show that urban expansion, unaccompanied by incentives for social, development added to economic, diversification leads to a situation of vulnerability to social groups in different parts of the city, where urban poverty presents itself in a perverse, way, creating a process of struggle, resistance and survival in urban space. Like this, there is a need for intervention by the public authorities, to soften the problems caused by this urban phenomenon.